DESIGN OF BUILDING CONDITION LEARNING MODELS SEMAPHORE PASSWORDS BY USING VISUAL STUDIO PROGRAMMING - Zainal Syahlan; Sutrisno Sutrisno; Deni Kristanto; Muhammad Syaifi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The design of Semaphore Password Learning Mode Using Visual Studio Programming is an application designed for semaphore coding learning. So far, learning has been done manually by means of drills from the instructor. With this application is expected to accelerate the learning process. Learning is done by clicking the alphabet button in the application, then the system will display the image of the letters in the application. To test skills, it can be done by the instructor sending practice questions to the server application, then the students will answer in the client application. In making the application the author uses the System Development Live Cycle (SDLC) in building software. Keywords: Semaphore and Lesson Application.